2020
DOI: 10.1038/s41598-020-72748-3
|View full text |Cite
|
Sign up to set email alerts
|

Topical ripasudil stimulates neuroprotection and axon regeneration in adult mice following optic nerve injury

Abstract: Optic nerve injury induces optic nerve degeneration and retinal ganglion cell (RGC) death that lead to visual disturbance. In this study, we examined if topical ripasudil has therapeutic potential in adult mice after optic nerve crush (ONC). Topical ripasudil suppressed ONC-induced phosphorylation of p38 mitogen-activated protein kinase and ameliorated RGC death. In addition, topical ripasudil significantly suppressed the phosphorylation of collapsin response mediator protein 2 and cofilin, and promoted optic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…The phosphorylation of CRMP2 is known to be associated with many neurodegenerative diseases (Cole et al, 2007;Menon et al, 2011;Zhao et al, 2020). A significant change in the phosphorylation level, but not in the protein level of CRMP2, has been reported in a mice 7 days after ONC (Nishijima et al, 2020), and a previous study reported the suppression of axonal degeneration in CRMP2KI/KI mice (Kinoshita et al, 2019), resulting in axonal stabilization. Mice injected with bi-cistronic adeno-associated viral (AAV2) vectors encoding a mutant phospho-resistant version of CRMP2 (CRMP2T555A) in RGCs showed neuroprotective effects in the retina and suppression of axonal degeneration after partial optic nerve injury (Chiha et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…The phosphorylation of CRMP2 is known to be associated with many neurodegenerative diseases (Cole et al, 2007;Menon et al, 2011;Zhao et al, 2020). A significant change in the phosphorylation level, but not in the protein level of CRMP2, has been reported in a mice 7 days after ONC (Nishijima et al, 2020), and a previous study reported the suppression of axonal degeneration in CRMP2KI/KI mice (Kinoshita et al, 2019), resulting in axonal stabilization. Mice injected with bi-cistronic adeno-associated viral (AAV2) vectors encoding a mutant phospho-resistant version of CRMP2 (CRMP2T555A) in RGCs showed neuroprotective effects in the retina and suppression of axonal degeneration after partial optic nerve injury (Chiha et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Several studies using different ROCK inhibitors focused on axonal regeneration after optic nerve injury. These ROCK inhibitors which have axonal regeneration effects include Y-27632, Y-39983, netarsudil, and ripasudil [ 16 19 ]. Among them, it was shown that ripasudil suppressed the phosphorylation of cofilin, a depolymerizing protein [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This provides the notion that the inability of CNS neurons to regenerate is an intrinsic property (He and Jin, 2016). Indeed, a large body of research now supports that manipulating intrinsic factors involved in CNS axon regeneration can promote robust axon regeneration in one of the popular CNS injury models, optic nerve crush (ONC) (Park et al, 2008;Smith et al, 2009;Norsworthy et al, 2017;Kondo et al, 2019;Thompson et al, 2019;Nishijima et al, 2020;Wang et al, 2020).…”
Section: Differential Nerve Injury Responses In the Peripheral And Ce...mentioning
confidence: 99%
“…Depending on the extent of axonal injury, 27-90% of RGCs can survive at two weeks post-injury; however, RGCs are not capable of spontaneously regenerating their axons after injury (Johnson and Tomarev, 2010;Sengottuvel et al, 2011). Therefore, RGCs are considered CNS neurons, and ONC has been widely used as an in vivo CNS injury model to study molecular mechanisms of neuronal survival and axon regeneration in the CNS (Park et al, 2008;Smith et al, 2009;Kondo et al, 2019;Thompson et al, 2019;Nishijima et al, 2020;Wang et al, 2020).…”
Section: Optic Nerve Crush Modelmentioning
confidence: 99%
See 1 more Smart Citation